Corporate governance in times of Venture capital - Porto Urrutia, José Miguel (2021)
The importance of having good corporate governance policies that respond to the particularities of the company is indisputable, especially in capital structures (such as startups), whose special dynamics in the industry (of venture capital) generate a high risk of harming the interests of disadvantaged groups (such as minority shareholders). In addition, there is a risk of unduly influencing management, due to the privileged position that certain groups hold (such as investors with a high financial capacity).In this order of ideas, this article exposes the challenges and complexities that the venture capital industry is going through, mainly in the Peruvian startup market. Likewise, the author analyzes some proposals for good corporate governance, in order to outline a starting point in the search for practices and policies that allow the consolidation of the figure in the country.